Cytotoxic Pentacyclic Triterpenoids from Prinsepia utilis - Guan, Bin; Peng, Cheng-Cheng; Zeng, Qi; Cheng, Xiang-Rong; Yan, Shi-Kai; Jin, Hui-Zi; Zhang, Wei-Dong (Planta Medica, 2013)
Phytochemical investigation of the aerial parts of Prinsepia utilis Royle resulted in the isolation and identification of ten pentacyclic triterpenoids, including two new triterpenoids, 2α-O-trans-p-coumaroyl-3β,19α-dihydroxy-urs-12-en-28-oic acid (1) and 2α-O-cis-p-coumaroyl-3β,19α-dihydroxy-urs-12-en-28-oic acid (2), along with eight known pentacyclic triterpenoids (3–10). The structures were elucidated by extensive spectroscopic methods and by comparison to previously reported spectroscopic data. Most of these compounds showed significant cytotoxic activities against four human cancer cell lines (A549, HCT116, MDA-MB-231, and CCRF-CEM), and the structure-activity relationships are also discussed.
Keywords: Prinsepia utilis; Rosaceae; triterpenoids; cytotoxicity